Evaluation of the Effect of Two Polishing Techniques and Thermocycling Process on Surface Roughness, Hardness, and Color Stability of Composites - Fidan, Muhammet; Dereli, Zeynep (UI Scholars Hub, 2022)
Objectives: The aim of this study was to evaluate the effect of two polishing techniques and 10.000 thermocycles on the color stability, surface roughness, and hardness of two nanohybrid (Tetric N-Ceram, Escom100) and one bulkfill (Filtek) resin composites. Methods: A total of 60 specimens were prepared using three resin composites and 20 discs from each composite. Specimens for each composite were randomly divided into two different polishing groups (Optrapol rubber and Sof-Lex discs) (n=10). Surface roughness (Ra, μm), microhardness (VHN), and color change (ΔE00) values were measured pre- and post-thermocycling. Two-way analysis of variance (ANOVA) was used to evaluate the effect of independent variables. Bonferroni test was used for multiple comparisons (p<0.05). Results: Escom100 with Sof-Lex found the highest mean ΔE00 and Filtek bulk-fill composite with Optrapol found the lowest mean ΔE00. Escom100 with Sof-Lex exhibited the lowest Ra values in all groups. Sof-Lex discs exhibited smoother surfaces than Optrapol in all groups.. Among the polishing groups, Optrapols’ VHN values were higher than Sof-Lex’s (p<0.05). Conclusions: Filtek bulk-fill with Optrapol in terms of color change and microhardness; Escom100 (nanohybrid) with Sof-Lex in terms of smoothness, can be recommended for clinical use. After thermocycling, surface roughness values increased and surface hardness values decreased in all composite resins.